2021
DOI: 10.6007/ijarbss/v11-i7/10488
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Perception of Students’ Readiness towards Online Learning During Covid-19 Pandemic

Abstract: Pandemic COVID-19 has given a significant impact and change the normal way of live whereby online learning has become the main way to teach and learn. In line with the emerging use of online learning, it is crucial to identify whether the students are ready and fit enough for online class or not. By knowing the level of readiness towards online learning, the educators can make full use of online learning in order to help the students to gain knowledge, apply the knowledge, upgrade their skills and performed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…This finding may be because the target population of this study were students enrolled in STEM subjects who are conversant with personalisation of learning; problem-based learning; rigorous learning; career, technology, and life skills; school community and belonging; external community; staff foundations; and external factors being the elements of inclusive STEM education (LaForce et al, 2016). This finding aligns with Forson and Vuopala (2019) and Kamaruzaman et al (2021), revealing that students had a positive attitude towards online learning. Ndlovu and Meyer (2019) stressed that preparedness is a major requirement for meaningful learning in an online environment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding may be because the target population of this study were students enrolled in STEM subjects who are conversant with personalisation of learning; problem-based learning; rigorous learning; career, technology, and life skills; school community and belonging; external community; staff foundations; and external factors being the elements of inclusive STEM education (LaForce et al, 2016). This finding aligns with Forson and Vuopala (2019) and Kamaruzaman et al (2021), revealing that students had a positive attitude towards online learning. Ndlovu and Meyer (2019) stressed that preparedness is a major requirement for meaningful learning in an online environment.…”
Section: Discussionsupporting
confidence: 80%
“…Technology users should also be interested in using technology as a learning tool and teaching platform for strengthening the education system globally (Forson & Vuopala, 2019;Ndlovu & Meyer, 2019;UNESCO, 2021). The availability and use of technology in teaching practices are essential in the COVID-19 era, while it remains essential to research students' preparedness for online teaching and learning Kamaruzaman et al, 2021). These constitute an element to be considered if the goals of STEM education are achieved through online teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, factors including 'instructional design' and 'students' perception' were overlapping themes in the present study. Initial research on students' perceptions exhibited students' prefer- ence for offline classes and the requirement of structured guidance irrespective of advanced technology (9,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…This includes planning and organizing their tasks and reminding themselves to study or complete their assignments on time. Kamaruzaman et al (2021) found that students preferred structured assignments as well as constant reminder from their lecturers to help them gain relevant skills for online learning. Students also need to avoid any distractions such as by switching off their phones, which could be a major challenge for these millennials (Amin et al, 2020;Friedman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%